P035: Impact of EMS direct referral to community care on emergency department utilization. (May 2019) - Dukelow, A.; Lewell, M.; Loosley, J.; Pancino, S.; Van Aarsen, K.
Abstract : Introduction : The Community Referral by Emergency Medical Services (CREMS) program was implemented in January 2015 in Southwestern Ontario. The program allows Paramedics interacting with a patient to directly refer those in need of home care support to their local Community Care Access Centre (CCAC) for needs assessment. If indicated, subsequent referrals are made to specific services (e.g. nursing, physiotherapy and geriatrics) by CCAC. Ideally, CREMS connects patients with appropriate, timely care, supporting individual needs. Previous literature has indicated CREMS results in an increase of home care services provided to patients.Methods : The primary objective of this project is to evaluate the impact of the CREMS program on Emergency Department utilization. Data for all CCAC referrals from London-Middlesex EMS was collected for a thirteen month period (February 2015-February 2016). For all patients receiving a new or increased service from CCAC the number of Emergency Department visits 2 years before referral and 2 years after referral were calculated. A related samples Wilcoxon Signed Rank Test was performed to examine the difference in ED visits pre and post referral to CCAC.Results : There were 213 individuals who received a new or increased service during the study timeframe. Median [IQR] patient age was 77 [70-85.5]. 113/213 (53%) of patients were female. The majority of patients 135/213 (63.4%) were a new referral to CCAC. The median [IQR] number of hospital visits before referral was 3 [1-5] and after referral was 2 [0-4]. There was no significant difference in the overall number of ED visits before versus after referral (955 vs 756 visits, p = 0.051).Conclusion : Community based care can improve patient experience and health outcomes. Paramedics are in a unique position to assess patients in their home to determine who might benefit from home care services. CREMS referrals for this patient group showed a trend towards decreased ED visits after referral but the trend was not statistically significant.